KONSEP BUSINESS PROCESSE ENGINEERING GUNA PEMBENAHAN SISTEM DAN KINERJA BISNIS PERUSAHAAN MANUFAKTUR - Dani Eko Wiyono; Farham HM Saleh; Taufiq Immawan (Teknoin, 2016)
Business Process Re-engineering is a process of re-designing business processes to improve performance. Business Process Reengineering that can be applied to help improve small and medium businesses. Manufacturing companyis a company engaged in the manufacture of test equipment Soil, Concrete, Asphalt, Hydrology and Meteorology. Organizational structure comprised of the management and some parts. The parts that include production, logistics, finance, and marketing sections with each section consists of several workers. The equipment ordered by the customer and is prepared to do the production of the raw material on demand. Target market of the product is universities, private institutions, government agencies and personal. The problem that occurs is in operational management, a lot of processes are not controlled, the documentation that mess, which still manually recording, data is not integrated and persuahaan primitive culture. Objective use of the method is the concept of Business Process Reengineering is a processing system will be computerized for the sake of presenting information more quickly, accurately, effectively and efficiently, as well as improvements in operational management system in order to survive and thrive among the other competitors. Which is of course to increase customer satisfaction and product quality, improve the satisfaction of the supplier or partner for cost efficiency and improve the welfare and satisfaction of employees. The results of business process reengineering in the form of customer satisfaction, employee satisfaction and supplier satisfaction (3P) and the data are well documented and directed.